Sistem Antrian, Waktu Tunggu, dan Pelayanan Fast Track Rawat Jalan di RS X Kota Padang - Nurmaines Adhyka; Bun Yurizali; Intan Kamala Aisyiah (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2022)
The increasing numbers of outpatients resulted in increased queue system problems and patients waiting times. This issue happens due to the number of visitors exceed the capacity of health care facility. To shorten queues and waiting times, the hospital also gives fast track service for the patient with particular criteria. This research aims to discuss the queue system, waiting tine and service outpatient of fast track in the X Hospital of Padang City. The design of this research used the method of quantitative descriptive. The result of the research shows the queue system in the X Hospital of Padang City in a condition of 14% still found the patient was not in the queue. Whereas the waiting time to meet with the doctor got the result 20% the waiting time to meet with the doctor was very slow. In fast track service, age group categories are found that are not included in the criteria fast track service in the X Hospital of Padang City. This recommendation has a purpose to the hospital to rearrange the queue system of the waiting time can be minimalized and the hospital employee gives more attention to the criteria of the patient that include fast track service so that it can use based on the purpose.